Synchronous Pulse Generation in an Array of Three <tex Notation="TeX">$ \hbox{Er}^{3 +}$</tex> -Doped Fiber Lasers - L. C. Gomez-Pavon (IEEE Photonics Journal, 2012)
In this paper, we report the experimental study of synchronous nanosecond pulse generation in an array of three coupled erbium-doped ring fiber lasers. We obtain the pulse generation by means of an amplitude modulator placed in one of the cavities and through the nonlinear energy interaction between the modulated cavity and the other cavities. Synchronous pulse generation is achieved in the array by an appropriate selection of coupling ratio between the cavities and the matching of cavity lengths, as well as the frequency modulation. We confirm synchronous generation through the phase diagrams and the spectral emission.